Antiviral efficacy of orally delivered neoagarohexaose, a nonconventional TLR4 agonist, against norovirus infection in mice. (December 2020) - Kim, Minwoo; Lee, Ji-Eun; Cho, Hee; Jung, Hae-Gwang; Lee, Wooseong; Seo, Han Young; Lee, Soung-Hoon; Ahn, Dae-Gyun; Kim, Seong-Jun; Yu, Je-Wook; Oh, Jong-Won
Abstract: The neoagarohexaose (NA6) is an oligosaccharide that is derived from agarose, the major component of red algae cell walls, by enzymatic hydrolysis. Here we show that NA6 is a noncanonical Toll-like receptor 4 (TLR4) agonist with antiviral activity against norovirus. Its TLR4 activation was dependent on myeloid differentiation factor 2 (MD2) and cluster of differentiation 14 (CD14), leading to interferon-β (IFN-β) and tumor necrosis factor-α (TNF-α) production. This effect was abolished by TLR4 knockdown or knockout in murine macrophages. NA6 inhibited murine norovirus (MNV) replication with an EC50 of 1.5 μM in RAW264.7 cells. It also lowered viral RNA titer in a human hepatocellular carcinoma Huh7-derived cell line harboring a human norovirus subgenomic replicon. The antiviral activity of NA6 was mainly attributed to IFN-β produced through the TLR4-TRIF signaling pathway. NA6-induced TNF-α, which had little effect on norovirus replication per se, primed macrophages to mount greater antiviral innate immune responses when IFN signaling was activated. NA6 boosted the induction of IFN-β in MNV-infected RAW264.7 cells and upregulated IFN-regulatory factor-1, an IFN-stimulated gene. NA6 induced IFN-β expression in the distal ileum with Peyer's patches and oral administration of NA6 reduced MNV loads through activation of TLR4 signaling, highlighting its potential contribution to protective antiviral innate immunity against norovirus. Graphical abstract: Image 1